Pelatihan Kader Malaria Dalam Upaya Melakukan Pencegahan Malaria Di Wilayah Kerja Puskesmas Harapan Distrik Sentani Timur - Banne Tondok, santalia; Utami, Theresia F.C.T; Sunarti, Sunarti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Based on Minister of Health Regulation Number 41 of 2018 Article 5 concerning the implementation of Early Detection and Administration of Anti-Malarial Medication by Malaria Cadres in Areas with Special Situations, it is explained that cadres can provide Malaria examination and treatment using RDT. The aim is that Malaria Cadres can play an active role in controlling malaria in Nendali village which is well organized with the Harapan Community Health Center. The results obtained were an increase in people's knowledge and attitudes, namely before providing counseling activities and simulations, knowledge was assessed as good by 20 participants (80%), attitudes by 21 participants (84%) and after providing counseling activities and simulations, parents' knowledge was assessed as good by 25 participants (100%) and attitudes were rated as good by 25 participants (100%) regarding Malaria.